2017
DOI: 10.1101/169979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Image velocimetry and spectral analysis enable quantitative characterization of larval zebrafish gut motility

Abstract: 2 Summary StatementWe present a new image analysis technique using image velocimetry and spectral analysis that returns quantitative measures of gut contraction strength, frequency, and wave speed that can be used to study gut motility and other cellular movements. AbstractNormal gut function requires rhythmic and coordinated movements that are affected by developmental processes, physical and chemical stimuli, and many debilitating diseases. The imaging and characterization of gut motility, especially regardi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This enables investigation of the localization and cross-species dynamics of fluorescently labelled bacterial species as well as GI function such as motility and barrier function. Additionally, the gut is simply cut open, making it possible to remove the microbiota for 16S sequencing 85,86,87 . Zebrafish have a considerable advantage over mammalian models when it comes to GI research because of their external fertilisation, rapid development also early transparency, which make investigating GI function in vivo much simpler.…”
Section: Clinical Studies Of Asdmentioning
confidence: 99%
“…This enables investigation of the localization and cross-species dynamics of fluorescently labelled bacterial species as well as GI function such as motility and barrier function. Additionally, the gut is simply cut open, making it possible to remove the microbiota for 16S sequencing 85,86,87 . Zebrafish have a considerable advantage over mammalian models when it comes to GI research because of their external fertilisation, rapid development also early transparency, which make investigating GI function in vivo much simpler.…”
Section: Clinical Studies Of Asdmentioning
confidence: 99%
“…We showed previously that in zebrafish mutants lacking the ENS due to mutation in the ret gene, a bacterial strain is able to persist that would normally be outcompeted in the presence of intestinal flow forces [38]. Coordinated, ENS-regulated intestinal contractions begin in larval zebrafish at 4 dpf and are robustly established by 6 dpf [40,90]. Here we assayed intestinal transit as a functional readout of these contractions and showed that sox10 mutants have decreased intestinal transit even in the absence of their microbiota, identifying another primary defect in these mutants.…”
Section: The Chemical and Physical Environment Of The Intestine Shapes The Microbiotamentioning
confidence: 99%
“…patterns have been described in a number of different mammals includes cats, 3,4 rabbits, 56 pigs, 7 sheep, 8 and humans. [9][10][11] In other vertebrates, such as fish, there have been some detailed description of intestinal propagating activity, [12][13][14] and however, in comparison with mammals, our knowledge of gut motility in fish still remains relatively poor.…”
mentioning
confidence: 99%